2018
DOI: 10.1186/s12957-018-1531-2
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, delivery, and breastfeeding after total gastrectomy for gastric cancer: a case report

Abstract: BackgroundThe reports of pregnancy after total gastrectomy for gastric cancer are rare.Case presentationWe report a case of a 35-year-old woman, gravida 0, para 0, who became pregnant and delivered a baby 2 years and 6 months after laparoscopic-assisted total gastrectomy for early gastric cancer. Postoperatively, she showed a good progress during the follow-up and was continuously taking oral iron supplement and administered with methylcobalamin intramuscular injection. Two years after gastrectomy, she became … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The timing of surgery may be individualized, taking into account patient preferences, while clearly explaining the risks of delay 308 . Women of child-bearing age should be reassured that prophylactic gastrectomy is compatible with successful childbirth and breastfeeding 311 . Both laparoscopic and robotic total gastrectomy may be appropriate 309 , 312 .…”
Section: Gastric Adenocarcinoma and Proximal Polyposis Of The Stomachmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of surgery may be individualized, taking into account patient preferences, while clearly explaining the risks of delay 308 . Women of child-bearing age should be reassured that prophylactic gastrectomy is compatible with successful childbirth and breastfeeding 311 . Both laparoscopic and robotic total gastrectomy may be appropriate 309 , 312 .…”
Section: Gastric Adenocarcinoma and Proximal Polyposis Of The Stomachmentioning
confidence: 99%
“…Annual gastroscopic surveillance should be performed in these patients and in patients who are not fully fit for surgery 308 . Women of child-bearing age should be assured of the real chance of uncomplicated pregnancy with successful childbirth and breastfeeding after prophylactic gastrectomy 311 . Both laparoscopic total gastrectomy 309 and robotic total gastrectomy 312 were recently used for GAPPS treatment.…”
Section: Gastric Adenocarcinoma and Proximal Polyposis Of The Stomachmentioning
confidence: 99%
“…In pregnancy, the established etiological factors of gastric cancer remain up-to-date, with the mention that the physiological features of pregnancy can participate in neoplastic etiopathogenesis. Isobe et al demonstrated that estrogens, which increase during pregnancy, favor the growth of diffuse-type adenocarcinoma, and the immunosuppressive influence of pregnancy can be an additional factor in the development of the cancer [32,33].…”
Section: Diet and Eating Habitsmentioning
confidence: 99%